Intercultural Competence for College and University Students: A Global Guide for Employability and Social Change - G.P. Sabet, Peyman; Chapman, Elaine (Journal of International Students, 2022)
The book Intercultural Competence for College and University Students, coauthored by Caprice Lantz-Deaton and Irina Golubeva, comprises eight chapters and details how college and university students can become better prepared, both academically and socially, for their future careers. IC is discussed under the three main topics: how IC can contribute to a more peaceful world and enhance intercultural interaction, how it can contribute to the academic and career success of each individual, and how potential IC can mitigate such issues as “equality, diversity, and inclusion worldwide” (p. vii).